Correction to: COVID-19 biomarkers for severity mapped to polycystic ovary syndrome - Abu Saleh Md Moin (6189512) (2021)
Correction to: COVID-19 biomarkers for severity mapped to polycystic ovary syndrome https://doi.org/10.1186/s12967-020-02669-2, published online 22 December 2020. Following publication of the original article [1], the authors would like to correct the author group with regards to the equal contributions: Stephen L. Atkin and Alexandra E. Butler should be listed as joint senior authors. The author group has been updated above and the original article [1] has been corrected. The original article has been corrected. Other Information Published in: Journal of Translational Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s12967-021-02782-w